Contributions of Lower Niger River Basin Development Authority in Transfer of Agrochemical Technologies to Rice Farmers in Kwara State, Nigeria - Oyetoro John Oyewole; Salihu Abogude Aliyu (Cutting-edge Research in Agricultural Sciences Vol. 10, 2021)
The study investigated the contributions of Lower Niger River Basin Development Authority in transfer of agro chemical technologies to rice farmers in Kwara State Nigeria. This study identified the types of recommended agro-chemicals utilized in study area, and reasons some respondents were deviating from the use of recommended agro-chemical. Structured interview schedule was used for data collection from 178 Rice Farmers who were randomly selected from list of registered rice farmers with Lower Niger River Basin Development Authority in Kwara state. The data were analyzed using statistical tool such as means, percentages, frequency counts and Pearson Product Moment Correlation. Findings revealed the type of recommended agro-chemicals transferred to rice farmers were systemic (glyphosate, delsate, forceup), Selective (2.4D amine and Orizo plus), Non Systemic (paraquate, Paraforce, Grammmzone), Pre-emergence (Atrazine powder, Atrazine Liquid, Bentazone), Fungicides (Blasticdine and Karate) and Post-harvest (Lambacynolathin). The reasons farmers deviated from the use of agro-chemicals are non-availability, adaptation problem, danger involve in the use of agro-chemicals and high price. Agricultural show had highest weighted mean score (WMS) of 1.22 and it was ranked first (1st) as major source of information from LNRBDA. On the utilization of Agrochemicals to rice farmers; 2,4-D Amine and Orizo plus were the most utilized agrochemical under LNRBDA recommendation. Provision of protective gears was ranked 1st as the most way by which LNRBDA contributed to the transfer of agro Chemicals to the rice farmers. The study therefore recommended that effort should be made by the agency to make awareness and information available by activities of LNRBDA in mass media.